The efficacy and safety of general anesthesia vs. conscious sedation for endovascular treatment in patients with acute ischemic stroke: a systematic review and meta-analysis - Zhao, Jiashuo; Tan, Xin; Wu, Xin; Li, Jiaxuan; Wang, Shixin; Qu, Ruisi; Chu, Tianchen; Chen, Zhouqing; Liu, Jiangang; Wang, Zhong (Frontiers in Neurology, 2023)
Background: Endovascular thrombectomy (EVT) is an important treatment for patients with acute ischemic stroke (AIS). A number of studies have suggested that anesthesia type (conscious sedation versus general anesthesia) during intra-arterial treatment for acute ischemic stroke has implications for patient outcomes.Methods: PubMed, EMBASE, Cochrane Library and clinicaltrials.gov were searched for randomized controlled trials (RCTs) that were performed to evaluate general anesthesia (GA) and conscious sedation (CS) up to May 30, 2023. Review Manager 5.3 software was used to assess the data. The risk ratio (RR) and mean difference (MD) were analyzed and calculated with a fixed effect model.We pooled 930 patients from seven RCTs. We conducted a meta-analysis comparing the outcomes of GA and CS in the included trials. The rate of functional independence in the GA group was higher than that in the CS group (RR: 1.17, 95% CI: 1.00-1.35; P=0.04; I 2 =16%). The GA group had a higher successful recanalization rate than the CS group (RR: 1.15, 95% CI: 1.08-1.22; P<0.0001; I 2 =26%). The GA group had a higher pneumonia rate than the CS group (RR: 1.69, 95% CI: 1.22-2.34; P=0.002; I 2 =26%). In addition, there was no significant difference between GA and CS with respect to the National Institutes of Health Stroke Scale (NIHSS) score at 24 h (P=0.62), Modified Rankin Scale (mRS) score at 90 days (P=0.25), intracerebral hemorrhage (P=0.54), and mortality at 3 months (P=0.61).GA demonstrated superiority over CS in achieving successful recanalization and functional independence at 3 months when performing EVT in AIS patients. However, it was also associated with a higher risk of pneumonia. Further studies, particularly those with long-term follow-ups, are necessary to identify precise strategies for selecting the appropriate anesthetic modality in EVT patients.